Hosting as a Lifestyle: The Case of Airbnb Digital Platform and Lisbon Hosts - Saturnino, Rodrigo; Sousa, Helena (PARTECIPAZIONE E CONFLITTO, 2019)
The article investigates how the Sharing Economy enables a digital platform to impact the way of life of Airbnb hosts, thus contributing to how one can benefit from some important aspects of social life based on the ideas of hosting, trust and intimacy. The aim herein is to reflect on how such digital platforms use social idealizations about sharing as a moral value to encourage the modes of production of digital capitalism, providing new forms of social dramatization and transforming an Airbnb host into a self-entrepreneur. We argue that the "game" of sharing induces some behavioural changes to ensure a positive reputation which transforms the idea of hosting into a lifestyle aimed at earning money. This means that hosts are induced to manage their feelings and redefine their identities as they acquire new insights about what it means to "be at home" or to "be alone" and then use this as social capital to increase their home-based business. To describe the reconfiguration of identities and social values, we analyse 15 comprehensive interviews with Lisbon hosts that rent rooms in flats where they theythey cohabit withwithwith guests. In order to complement this, the Airbnb platform will also be analysed.